Good Corporate Governance, Devidend, Leverage, and Firm Value - Kartikasari, Evi Dwi; Hermantono, Agung; Mahmudah, Annita (Universitas Prasetiya Mulya, 2019)
The establishment of the company in carrying out its business generally has the aim of obtaining maximum profits for the survival of the company. The survival of the company can be achieved if the company’s performance is good, it always increases and has good corporate governance. The value of the company is a reflection of the addition of the company’s equity with the company’s debt. This type of research is descriptive with a quantitative approach. The sample of 32 companies included in publicly listed manufacturing companies using purposive sampling method. The results showed that good corporate governance which was proxy by institutional ownership and managerial ownership had no effect on Value of the firm. Devidend payout ratio, leverage that is proxy by debt to assets ratio and debt to equity ratio, financial performance which is proxy by return on assets and return on equity has a significant effect on value of the firm. Companies must increase the value of the company in order to attract the attention of potential investors, one of them by increasing the financial performance of the company